Mobile Forensic Analysis on IMO Messenger Application Using ACPO and NIJ Frameworks - Safitri, Yana; Firmansyah, Firmansyah; Mu’min, Muhammad Amirul (Insect (Informatics and Security): Jurnal Teknik Informatika, 2025)
The need for efficient digital forensic tools has become increasingly urgent with the rapid development of digital communication platforms. This study aims to compare forensic frameworks on the Android application IMO Messenger, focusing on the Association of Chiefs of Police (ACPO) and the National Institute of Justice (NIJ) frameworks. The research utilizes the forensic tools MOBILEdit Forensic Express and Autopsy. The primary objective of the study is to gather evidence related to a body-shaming case. The findings show that MOBILEdit Forensic Express Pro achieved a 100% extraction rate, while Autopsy managed only 3.33%. By adhering to the guidelines established by ACPO and NIJ, the data extraction process was conducted following legitimate and accountable procedures. The use of certified tools and appropriate methods ensured that the extracted data remained accurate, valid, and reliable. These findings contribute to advancing knowledge in mobile forensics for addressing cyberbullying, providing valuable insights for investigators.